Pemikiran Ekonomi Syariah Menurut Muhammad Abdul Mannan dan Muhammad Baqir Al-Sadr - Dewi Nur Ainiyah; A. Zaim Fachri; M. Zainal Abidin (Maliyah : Jurnal Hukum Bisnis Islam, 2019)
This article discusses Islamic economic thinking according to Muhammad Abdul Mannan and Muhammad Baqir as-Sadr. The purpose of writing this article is to find out the similarities and differences in the economic thought of Muhammad Abdul Mannan and Muhammad Baqir as-Sadr. This research is library research and is qualitative. The data were obtained through books, journal articles, and the internet, especially those discussing Islamic economics and the works of Muhammad Abdul Mannan and Muhammad Baqir as-Sadr. The data collected were analyzed comparatively. The study results conclude that Mannan and as-Sadr have the same thoughts in terms of income distribution to ensure the welfare of all elements of society in a country. The economic problem does not lie in production or the scarcity of resources, but rather due to unequal and unfair distribution due to the financial system that allows the exploitation of the strong against the weak. According to Abdul Mannan, the difference between Baqir and Mannan's thoughts is that production can combine the traditional economy and the market. At the same time, Baqir As Sadr only supports government planning and does not consider market forces. M. A. Mannan allowed private ownership, while Baqir Ash-Sadr limited private ownership to use rights only.